Nivel socioeconómico de mujeres en movilidad humana en la provincia de Pichincha sector Carapungo año 2020 2023” - Martínez Buitrón, Jenny Elizabeth (2024)
Human mobility has experienced a notable increase in recent years due to various factors, significantly affecting Latin American countries. Ecuador has become a prominent destination country, demonstrating remarkable solidarity by welcoming vulnerable people who have settled in several cities across the country. This thesis project aims to analyze the socioeconomic level of women in situations of human mobility in the province of Pichincha, specifically in the Carapungo neighborhood, during the period from 2020 to 2023. The objective is to identify the socioeconomic factors that affect these women and propose initiatives to improve their social and economic inclusion. The study is conducted using a mixed-methods approach, employing both qualitative and quantitative techniques. Structured interviews, surveys, and focus groups were carried out to collect relevant information. The research revealed that many of these women face significant barriers to social inclusion due to their migrant status and gender, which negatively impacts their self-esteem and quality of life. The study highlights the need to create policies and programs that promote the integration of migrant women into prefecture projects, aiming to improve their socioeconomic conditions and provide them with greater development opportunities. This study also seeks to change the perception of human mobility, combating stereotypes and fostering a more inclusive and equitable society. 4 In summary, this work addresses the challenges and opportunities for the social inclusion of migrant women in Pichincha, offering a comprehensive and well-founded perspective for the formulation of effective public policies. Specific statistics on the exact number of people in human mobility in Carapungo are not clearly detailed in the available sources. However, it is known that Quito, in general, hosts a large number of people in human mobility as the capital of the country. The province of Pichincha is home to nearly 108,000 refugees and migrants, making it one of the provinces with the highest numbers in Ecuador.